The sum Jose wants to compute is
3 + 6 + 9 + … + 993 + 996 + 999
but since each number is a multiple of 3, he can remove a factor of 3 from eac term:
3 (1 + 2 + 3 + … + 331 + 332 + 333)
Then it's clear that the sum contains 333 terms.
Let S be the value of the sum of the first 333 natural numbers:
S = 1 + 2 + 3 + … + 331 + 332 + 333
Reversing the order of terms has no effect on this value:
S = 333 + 332 + 331 + … + 3 + 2 + 1
Now notice that terms in the same position sum to 334:
1 + 333 = 334
2 + 332 = 334
3 + 331 = 334
and so on. This means that if we pair up terms in the positions and add them up, all we are doing is doubling the value of S on the left side, and adding up 333 copies of 334 on the right side:
2S = 334 + 334 + … + 334 + 334
2S = 333 × 334
Solve for S :
S = 333 × 334 / 2 = 55,611
Then the sum Jose is considering is 3 times this value,
3 + 6 + 9 + … + 993 + 996 + 999 = 166,833